Teacher density and student achievement in Swedish compulsory schools - Christian Andersson (Uppsala University, Department of Economics, 2007)
This paper analyzes how student achievement is affected by resource increases in the Swedish compulsory school due to a special government grant that was enforced in the academic year of 2001/02. The analysis is based on register data that contains all students that completed compulsory schooling (ninth grade) between 1998 and 2005. The results show that socio-economic variables explain a great deal of the variation in student achievement. The study also shows that the increased resources have not had a statistical significant positive effect on the average students achievement. This conclusion holds true when different measures of student achievement are used. Increased resources have however improved student achievement for students with low educated parents. If teacher density is increased with 10 percent students with low educated parents are expected to increase their grade point average ranking with about 0.4 percentile units.
urn:nbn:se:uu:diva-25358
Keywords: I21; 330; teacher density; student achievement; government grant; Bildungspolitik; Bildungsfinanzierung; Bildungsfinanzierung; Lehrkräfte; Bildungsertrag; Schweden